Indirect Targeting of Subthalamic Deep Brain Stimulation Guided by Stereotactic Computed Tomography and Microelectrode Recordings in Patients With Parkinson’s Disease - Tu, Po-Hsun; Liu, Zhuo-Hao; Chen, Chiung Chu; Lin, Wey Yil; Bowes, Amy L.; Lu, Chin Song; Lee, Shih-Tseng (Frontiers in Human Neuroscience, 2018)
Objective: Magnetic resonance imaging fusion techniques guided by frame-based stereotactic computed tomography and microelectrode recordings are widely used to target the subthalamic nucleus. However, MRI is not always available. The aim of this study was to determine whether the indirect targeting of the subthalamic nucleus for deep brain stimulation using frame-based stereotactic computed tomography and microelectrode recording guidance in patients with advanced idiopathic Parkinson’s disease was an effective and safe treatment and to determine the factors that contributed to outcome. Methods: Thirty-four consecutive patients with Parkinson's disease who were treated from 2010 to 2012 were enrolled in this retrospective cohort study. The patients were assessed with the Unified Parkinson’s Disease Rating Scale-part III (UPDRS-III) and other clinical profiles peri- and post-operatively. The horizontal and vertical distances between the midpoint of the head frame and the brain midline at the septum pellucidum level and the upper edge of the bilateral lens, respectively, on a thin-section brain computed tomography scan were defined as the horizontal and vertical deviations, respectively. Results: After the deep brain stimulation surgery, the patients’ UPDRS-III scores improved 48 ± 2.8% (range, 20%–81%) compared to the patients’ baseline off-levodopa scores. No surgery-associated complications were found. The mean recorded length difference of the subthalamic nucleus between the initial and final single microelectrode recording trajectories was 5.37 ± 0.16 mm (range, 3.99–7.50). Multiple linear regression analyses revealed that the increased lengths of the vertical (regression coefficient [B]: -0.0626; 95% confidence interval [CI]: -0.113 to -0.013) and horizontal deviations (B: -0.0497; 95% CI: -0.083 to -0.017) were associated with less improvement in the patients’ UPDRS scores. Conclusion: These results showed that the indirect targeting of the subthalamic nucleus for deep brain stimulation using frame-based stereotactic computed tomography and microelectrode recording guidance in patients with advanced idiopathic Parkinson’s disease was effective and safe. Greater symmetry of the head frame fixation resulted in better outcomes of the deep brain stimulation of the subthalamic nucleus in patients with Parkinson’s disease, especially when the horizontal deviation was 2 mm or less and the vertical deviation was 1 mm or less.